2020
DOI: 10.1021/acsenergylett.0c02203
|View full text |Cite
|
Sign up to set email alerts
|

Modular Design of Highly Active Unitized Reversible Fuel Cell Electrocatalysts

Abstract: A modular, multicomponent catalyst design principle is introduced and exemplified using a three-component, oxygen reduction reaction/oxygen evolution reaction (ORR/OER) catalyst designed for the oxygen electrode of unitized reversible fuel cells (URFCs). The catalyst system exhibited unprecedented catalytic performance in liquid electrolyte and in single unitized reversible fuel cell tests. The distinct components, each active for either ORR or OER, are prepared and optimized independently of each other and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…DMFCs use Pt-Ru catalysts [154] or Pt-Co/Pt-Ni catalysts [155]. RFCs can use PGM catalysts, but transition metal electrode catalysts are also under investigation [156].…”
Section: Electric Vehiclesmentioning
confidence: 99%
“…DMFCs use Pt-Ru catalysts [154] or Pt-Co/Pt-Ni catalysts [155]. RFCs can use PGM catalysts, but transition metal electrode catalysts are also under investigation [156].…”
Section: Electric Vehiclesmentioning
confidence: 99%
“…The oxygen evolution reaction (OER, 4OH − → 2H 2 O + O 2 + 4 e − ), as one of the most fundamental energy-intensive anodic reactions, plays an important role in many energy-related sustainable systems such as water-splitting devices [ 1 , 2 , 3 ], fuel cells [ 4 , 5 , 6 , 7 , 8 ], rechargeable metal–air batteries [ 9 , 10 , 11 ], and sustainable CO 2 reduction systems [ 12 , 13 , 14 ]. Unfortunately, the decisive OER process suffers from its intrinsically sluggish reaction kinetics due to their complicated multi-step proton-coupled electron transfer paths [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the resulting H 2 must be cleaned of carbon impurities before use, which adds complexity and costs. Electrochemical converters can not only synthesize H 2 of high purity without CO 2 by using renewable electricity (hydroelectricity, wind, solar …) but also use it to produce electricity via reversible fuel cells and electrolyzers (2H 2 O = 2H 2 + O 2 ) [ 4 , 5 ]. Significant advances have demonstrated that different electrocatalytic materials can enable water electrolysis in acidic or alkaline media closely at its thermoneutral cell voltage of 1.45 V [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%